Psikedukasi : Sosiaisasi Dampak Kriminal Bullying Sesuai UU Yang Ada Terhadap Siswa SMP Maria Monica Bekasi Bagi Kesehatan Mental - Alsa Zahra Fahira; Ferdy Muzammil; Angellita Arnettha Putri (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Bullying and intimidation are several forms of bullying that we often encounter on campus, neighbors and in the office, especially in the school environment. Bullying can be done in various ways, including physical, mental and social media. The targets of bullying are usually accepted or experienced by weak people who cannot resist these actions. Bullying itself is regulated in article 76C of Law Number 35 of 2014. The focus of the problem that we will examine is